Identification of Symptoms and Frequency of Disease Occurrence in Groundnut Plants (Arachis hypogaea L.) - Niken Nur Kasim; Nurul Wiridannissa; Sri Sukmawati Djafar; Prihatin Prihatin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Groundnut (Arachis hypogaea L.) is a crop plant that has an essential role in several food industries because it has high nutritional content, especially protein, and fat. One of the limiting factors in efforts to increase peanut production is the disturbance of plant-disrupting organisms (PDO). Preventive efforts that can be made to minimize yield losses due to pest problems in peanut plants include inventory activities and direct observations in the field. This study aims to assess the biological aspects of important diseases in peanut plants as an initial step in making pest control decisions. Observations were conducted on a 748 m2 farmer's field in Purangi Village, Sendana Sub-district, Palopo City. The field was divided into two main plots, without using maize barrier (B0) and using maize barrier (B1), and six subplots (P1-P6). Groundnut disease symptoms were determined through identification based on the signs and symptoms of the attack. Disease symptoms found in peanut plants were chlorosis, necrosis, spotting, mosaic, curling, and wilting. Mosaic and necrosis symptoms were the most dominant symptoms with the highest frequency of occurrence at 50 times, while chlorosis, curling, stripes, and wilting symptoms were the lowest symptoms with the least frequency of occurrence in peanut plantations at under 25 times.